Accuracy of Goodsall’s Rule in Perianal Fistulas – Correlation with Mr Fistulogram - Pavan Kumar N1 ,Venkatraman Indiran2 , Ramachandra Prasad3 , Prabakaran Maduraimuthu4 ,Krishna Prasa (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Perianal fistula is one of the common gastrointestinal pathology with significant morbidity.Goodsall’s rule states that the posterior perianal fistulas have the fistulous tract that opens into the anal canalin the midline posteriorly, sometimes taking a curvilinear course and anterior perianal fistulas will have aradial fistulous tract.Objectives: To assess the accuracy of Goodsall’s rule in perianal fistulas on comparison with MagneticResonance (MR) fistulogram findings.Materials and Methods: A total of 45 cases with perianal fistula underwent pre-operative MR Fistulogramassessment. Fistulas were divided into anterior and posterior fistulas based on MR Fistulogram findings.Accuracy of Goodsall’s rule in all the perianal fistulas visualised on MRI was assessed.Results: Out of 45 patients, 10(22.2%) patients had anterior fistulas and rest of 35(77.8%) patients hadposterior fistulas. Goodsall’s rule was valid in 28(62.2%) patients. Seventeen (37.8%) patients did not followGoodsall’s rule. Goodsall’s rule was found to be more accurate in anterior fistulas than posterior fistulas.Conclusion: MR Fistulogram has high accuracy of detecting perianal fistulas. Goodsall’s rule may not bevalid in all the cases of perianal fistulas. Goodsall’s rule is more applicable in anterior fistulas. Posteriorfistulas do not strictly adhere to Goodsall’s rule with many of them showing linear tracts. This informationis useful for pre-operative planning of fistula treatment.